Differential Expression of dmrt1 in Astyanax scabripinnis (Teleostei, Characidade) Is Correlated with B Chromosome Occurrence - Castro, Jonathan Pena; Hattori, Ricardo Shohei; Yoshinaga, Tulio Teruo; Zerbinato de Adrade Silva, Duilio Mazzoni [UNESP]; Foresti, Fausto [UNESP]; Santos, Mateus Henrique; Almeida, Mara Cristina; Artoni, Roberto Ferreira (Mary Ann Liebert, Inc, 2018)
Astyanax is an abundant fish genus in South America. Some species of this group are characterized by the presence of B chromosomes and absence of morphologically differentiated sex chromosomes. In this study, we used quantitative real-time polymerase chain reaction to characterize mRNA expression of dmrt1 in Astyanax scabripinnis gonads. Maturing gonads of males with the B chromosome overexpressed dmrt1. Our findings suggest that B chromosomes may have an adaptive role in A. scabripinnis sex determination and maintenance.
Keywords: dmrt1; sex determination; sex differentiation; sex ratio; hermaphroditism; fish